Uruguay: A Woman Remembers - Randall, Margaret (Social justice, 2015)
This conversation between Emilia Carlevaro, a longtime political activist and Uruguayan member of the Latin American Organization of the Families of the Disappeared, and Margaret Randall, a feminist poet, writer, photographer, and social activist is a valuable history with lessons for new generations of activists. It explores the shared experience of Argentina, Chile, and Uruguay. Their revolutionary cadre often crossed borders, as did Operation Condor, the regional paramilitary organization charged with destroying them.